THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION ON PT. BANK BUKOPIN KABUPATEN SIDRAP, SULAWESI SELATAN - Pandi Putra; Amrial Amrial (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2021)
This research aims to find out and analyze how much the influence of service quality on customer satisfaction on PT. Bank Bukopin Sidrap. The Analysis method used in this study is multiple linear analysis. Where the method of collecting data is through Observation, Questionnaires, and interviews. The determination of the sample was determined by solving the formula and obtained by 344 respondents. The results of this study showed that the results showed that there is a tangible influence, reliability, responsiveness, assurance, and, empathy on customer satisfaction in PT. Bank Bukopin Sidrap. This is evidenced by the statistic Fhitung result of 9,339. The results of the R2 determinant test in this study obtained a determinant value of R2 of 0.621 which means that the magnitude of the influence of tangible variables, reliability, responsiveness, assurance, and empathy on customer satisfaction is 62.1% and the remaining 37.9% described other variables that are not included in this study.